+0  
 
0
151
3
avatar

Solve for a in terms of b and c, assuming b≠3:

ab = 3a +2b + c.
 

Guest Feb 14, 2018
 #1
avatar+93038 
+2

ab   =  3a + 2b + c   subtract  3a from both sides

 

ab - 3a   =   2b + c       factor the left side

 

a (b - 3)   =   2b + c        divide both sides by  ( b - 3)

 

a  =  [ 2b + c  ] / [  [ b - 3  ]

 

 

cool cool cool

CPhill  Feb 14, 2018
 #2
avatar+374 
+2

ab=3a+2b+c

ab-3a=2b+c

a(b-3)=2b+c

a=2b+c/b-3

 

smileysmileysmiley

qualitystreet  Feb 14, 2018
edited by qualitystreet  Feb 14, 2018
 #3
avatar+93038 
0

Good job, QS.....!!!

 

cool cool cool

CPhill  Feb 14, 2018

13 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.